Design for Wellness: Therapeutic Approaches in Workplace Interiors - Meghna Jain; Deepti Pande Rana; Pooja Singh (International Journal of Environmental Planning and Development Architecture, 2024)
The modern workplace is increasingly recognized as a pivotal environment influencing employee well-being, productivity, and overall organizational success. This research paper delves into the integration of therapeutic design principles within office spaces to foster a healthier, more supportive environment for employees. The study investigates how strategic interior design can promote physical and mental well-being, reduce stress, and enhance employee satisfaction and productivity. By incorporating elements such as natural lighting, biophilic design, ergonomic furniture, and thoughtful spatial layouts, workplaces can be transformed into spaces that support holistic wellness. The research examines various therapeutic design strategies, including the use of calming color palettes, natural materials, acoustic treatments, and flexible workspaces that encourage movement and collaboration. These approaches are analyzed through a combination of qualitative and quantitative methods, drawing on case studies from a range of industries to illustrate the effectiveness of these design choices. The findings reveal that therapeutic design not only enhances the aesthetic and functional aspects of office interiors but also plays a crucial role in improving employee morale, and engagement, and reducing absenteeism. The study emphasizes the importance of creating environments that cater to sensory needs and foster a sense of belonging, comfort, and psychological safety. It also discusses the economic benefits of investing in wellness-oriented design, such as reduced healthcare costs and higher retention rates. Ultimately, this paper provides valuable insights for interior designers, architects, and business leaders looking to cultivate more sustainable, inclusive, and well-being-oriented workplaces. By aligning design with wellness objectives, organizations can create environments that promote both individual and collective thriving, leading to improved overall performance, a healthier workforce, and a more resilient organization
Keywords: Employee Well-Being; Therapeutic design; healthier workforce; holistic wellness; productivity; resilient organization; therapeutic design strategies